URGENSI SERTIFIKASI HALAL BAGI USAHA MINUMAN OLAHAN KOPI - Wimala Pastika, Dinda Bhawika; Bambang Sugeng Ariadi Subagyono; Zahry Vandawati Chumaida (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2023)
Kopi merupakan produk minuman dari biji kopi yang telah digiling lalu kemudian diseduh menggunakan banyak metode dan merupakan salah satu minuman paling populer yang dikonsumsi hampir semua kalangan. Pada era ini produk olahan kopi yang ditawarkan sangat beragam dari kopi murni hingga kopi sachet dengan aneka rasa. Selain itu, Konsumen produk kopi dengan sangat mudah bisa mendapatkan dan mengonsumsi kopi yang diinginkan. Dengan hal ini dimana Indonesia ialah negara dengan penduduk yang kebanyakan seorang muslim, maka Jaminan Produk Halal untuk produk olahan kopi sangat dibutuhkan bagi konsumen maupun pelaku usaha. Negara di tahun 2014 sudah mengundangkan UU No. 33 Tahun 2014 perihal Jaminan Produk Halal (JPH) yang bertujuan untuk melindungi hak konsumen muslim. Upaya pelaksanaan Jaminan Produk Halal (JPH) ditandai dengan label halal dan sertifikat yang diterbitkan Badan Penyelenggara Jaminan Produk Halal yang bernaung di Kementerian Agama namun pelaksanaan sertifikasi dan labelisasi halal dinilai masih sangat kurang dilihat dari mayoritas pengusaha yang tidak mendata produknya untuk mendapatkan label halal dan sertifikat terutama pengusaha dengan skala bisnis mikro kecil menengah. Coffee is a beverage product from coffee beans that have been ground and then brewed using many methods. Coffee is one of the most popular drinks consumed by almost everyone. The coffee industry has grown a lot compared to ten years ago. Nowadays, the processed coffee products offered are very diverse, from pure coffee to sachet coffee with various flavors. Consumers of coffee products can very easily get and consume the coffee they want. Considering that Indonesia is a country with a population that is mostly Muslim, the Halal Product Guarantee for processed coffee products is very much needed by consumers and businesses. The state in 2014 has enacted Law No.33/2014 regarding JPH (Halal Product Guarantee). The law aims to protect the rights of Muslim consumers from the distribution of processed food and medicinal drinks which are consumed in Indonesia. Halal Product Guarantee is a regulation that is mandatory (mandatory) implemented by all business actors who trade their products in Indonesia, including products originating from abroad. Efforts to implement Halal Product Assurance (JPH) are marked by a halal label and a certificate issued by the Halal Product Assurance Organizing Body under the auspices of the Ministry of Religion but the implementation of halal certification and labeling is considered to be still lacking, seen from the majority of entrepreneurs who do not record their products to obtain halal labels and certificates, especially entrepreneurs with micro, small and medium scale businesses.